Habitual Fish Oil Supplementation and Risk of Incident Inflammatory Bowel Diseases: A Prospective Population-Based Study - Huang, Xiaoxu; Li, Yin; Zhuang, Pan; Liu, Xiaohui; Zhang, Yu; Zhang, Pianhong; Jiao, Jingjing (Frontiers in Nutrition, 2022)
Background: Inflammatory Bowel Diseases (IBDs) have been emerging in recent years with the advance of global industrialization and diet pattern transformation. Marine n-3 polyunsaturated fatty acids (n-3 PUFAs), enriched in fish oils, have well-known human health promotion. Evidence on the association of fish oil supplementation with the risk of developing IBDs was scarce. This study aimed to examine the association between fish oil supplement use and the risk of developing inflammatory bowel diseases (IBDs) among the general population. Methods: We conducted a prospective cohort study of 447,890 participants aged 40-69 years from UK Biobank. A touch screen questionnaire was used to get the data about fish oil intake at baseline. Incident diagnoses of IBDs were ascertained by the International Classification of Diseases (ICD-9 and ICD-10) or self-report. Cox proportional hazards model was applied to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) of developing IBDs and its subtypes. Results: We documented 1,646 incident cases of IBDs, including 533 incident cases of Crohn’s disease (CD) and 1,185 incident cases of ulcerative colitis (UC) during an average of 8.0 years of follow-up. After multivariate adjustment, the use of fish oil was associated with 12% lower risk of IBDs (HR: 0.88, 95% CI: 0.78-0.99, P=.03) compared with nonconsumers. For subtypes of IBDs, fish oil supplementation was inversely associated with 15% lower risk of UC (HR: 0.85, 95% CI: 0.75-0.99, P=.02) but was not correlated with the risk of CD (P=.22). Besides, fish oil supplementation showed a significant inverse correlation with baseline CRP levels (β= -0.021, P<0.001) and a positive association with baseline albumin levels (β=0.135, P<0.001) after adjustment for multiple variates. Conclusions: Habitual intake of fish oil supplements was associated with a lower risk of IBDs and UC. Fish oil users tended to have lower baseline C-reactive protein levels and higher baseline albumin levels compared with non-users. It provided that fish oil supplement use may be recommended for the prevention and control of IBDs.